Perlindungan Hukum Bagi Saksi Tindak Pidana Pembunuhan - Fariaman Laia (Syntax Idea, 2021)
The purpose of this research is what is there to know and about the protection of the Law for Witnesses of Criminal Crimes. In this study using a type of normative legal research with the collection and inventory of legal data as well as, the analysis is qualitative. From which research the author, it can be about knowing the law around witnesses in criminal acts in the midst of physical protection, among others: supervision and escort, body security equipment, services and moreover, the cost of changing lives during the protection period, the cost of transportation changes and places during protection, protection in safe houses, realah and new identities, and legal protection, among others : information on the outcome of a case or court decision related to the report of who gave as much as half with internal regulations and laws and regulations, and laws and regulations. Goods and legal protection efforts in the case of regional and external criminal cases, criminal by means of legal means mainly, both criminal law materill, criminal lawmil or regional law where criminal criminal system for purposes and non-criminal or efforts outside the law more criminal minutes on the nature, antidote, outside let alone occur. The main point of this effort is the conducive factors that cause crime.